# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }-\frac {y^{\prime }}{t}+\frac {y}{t^{2}} = \frac {1}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \left \{\begin {array}{cc} 4 & 0\le t <2 \\ 0 & 2\le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \left \{\begin {array}{cc} t & 0\le t <1 \\ 0 & 1\le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 5 \,{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2-{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-5 y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = 27 t^{2}+9
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{2} = 5 \cos \left (t \right )+2 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = 8 \cos \left (4 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+10 y = 2 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 y = 27 t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 2 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 4+3 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2 \cos \left (t \right )+t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{2} = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{2} = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }+y = \cos \left (t \right ) t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{2}-\frac {y}{2 \sqrt {t}}+\left (2 t y-\sqrt {t}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {t}{\sqrt {t^{2}+y^{2}}}+\frac {y y^{\prime }}{\sqrt {t^{2}+y^{2}}} = 0
\] |
✓ |
✓ |
|
\[
{}y \cos \left (t y\right )+t \cos \left (t y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \sec \left (t \right )^{2}+2 t +\tan \left (t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 t y^{2}+y^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t -y \sin \left (t \right )+\left (y^{6}+\cos \left (t \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \sin \left (2 t \right )+\left (\sqrt {y}+\cos \left (2 t \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\ln \left (t y\right )+\frac {t y^{\prime }}{y} = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{t y}+\frac {t \,{\mathrm e}^{t y} y^{\prime }}{y} = 0
\] |
✓ |
✓ |
|
\[
{}3 t^{2}-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-1+3 y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+2 t y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {3 t^{2}}{y}-\frac {t^{3} y^{\prime }}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}2 t +y^{3}+\left (3 t y^{2}+4\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-\frac {1}{y}+\left (\frac {t}{y^{2}}+3 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y+\left (t^{2}+y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y^{3}+\left (1+3 t^{2} y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (y\right )^{2}+t \sin \left (2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 t^{2}+3 y^{2}+6 t y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{t} \sin \left (y\right )+\left (1+{\mathrm e}^{t} \cos \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 t^{2} y+3 y^{2}-1+\left (t^{3}+6 t y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-2 t y^{2} \sin \left (t^{2}\right )+2 y \cos \left (t^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t -y^{2} \sin \left (t y\right )+\left (\cos \left (t y\right )-t y \sin \left (t y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1-y^{2} \cos \left (t y\right )+\left (t y \cos \left (t y\right )+\sin \left (t y\right )\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}2 t \sin \left (y\right )-2 t y \sin \left (t^{2}\right )+\left (t^{2} \cos \left (y\right )+\cos \left (t^{2}\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (3+t \right ) \cos \left (y+t \right )+\sin \left (y+t \right )+\left (3+t \right ) \cos \left (y+t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2 t^{2} y \cos \left (t^{2}\right )-y \sin \left (t^{2}\right )}{t^{2}}+\frac {\left (2 t y+\sin \left (t^{2}\right )\right ) y^{\prime }}{t} = 0
\] |
✓ |
✓ |
|
\[
{}-\frac {y^{2} {\mathrm e}^{\frac {y}{t}}}{t^{2}}+1+{\mathrm e}^{\frac {y}{t}} \left (1+\frac {y}{t}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t \sin \left (\frac {y}{t}\right )-y \cos \left (\frac {y}{t}\right )+t \cos \left (\frac {y}{t}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y^{2}+2 t^{2} y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+\frac {y}{t^{2}}-\frac {y^{\prime }}{t} = 0
\] |
✓ |
✓ |
|
\[
{}2 t y+3 t^{2}+\left (t^{2}-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+5 t -y-\left (t +2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y}-2 t y+\left (t \,{\mathrm e}^{y}-t^{2}\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}2 t y \,{\mathrm e}^{t^{2}}+2 t \,{\mathrm e}^{-y}+\left ({\mathrm e}^{t^{2}}-t^{2} {\mathrm e}^{-y}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-2 \sin \left (2 t \right )+\left (1+2 t y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (t \right )^{2}-\sin \left (t \right )^{2}+y+\left (\sec \left (y\right ) \tan \left (y\right )+t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {1}{t^{2}+1}-y^{2}-2 t y y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}\frac {2 t}{t^{2}+1}+y+\left ({\mathrm e}^{y}+t \right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}-2 x -y \cos \left (x y\right )+\left (2 y-x \cos \left (x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-4 x^{3}+6 y \sin \left (6 x y\right )+\left (4 y^{3}+6 x \sin \left (6 x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y+t^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (2 \,{\mathrm e}^{t}+4 t \right )+3 \left ({\mathrm e}^{t}+t^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (2 t -y \,{\mathrm e}^{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y+y^{2}-t^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+2 t^{2}+\left (t^{2} y-t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}5 t y+4 y^{2}+1+\left (t^{2}+2 t y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}5 t y^{2}+y+\left (2 t^{3}-t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t +\tan \left (y\right )+\left (t -t^{2} \tan \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t -y^{2} \sin \left (t y\right )+\left (\cos \left (t y\right )-t y \sin \left (t y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-1+{\mathrm e}^{t y} y+y \cos \left (t y\right )+\left (1+{\mathrm e}^{t y} t +t \cos \left (t y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t +2 y+\left (2 t +2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {9 t}{5}+2 y+\left (2 t +2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t +\frac {19 y}{10}+\left (\frac {19 t}{10}+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{2} = \frac {t}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = t y^{2}
\] |
✓ |
✓ |
|
\[
{}2 t y^{\prime }-y = 2 t y^{3} \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}t y^{\prime }-y = t y^{3} \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = \frac {\cos \left (t \right )}{\sqrt {y}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = \sqrt {y}\, \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{t} = t y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{t} = \frac {y^{2}}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{t} = \frac {y^{2}}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{t} = t^{2} y^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}\cos \left (\frac {t}{y+t}\right )+{\mathrm e}^{\frac {2 y}{t}} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \ln \left (\frac {t}{y}\right )+\frac {t^{2} y^{\prime }}{y+t} = 0
\] |
✓ |
✓ |
|
\[
{}2 \ln \left (t \right )-\ln \left (4 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2}{t}+\frac {1}{y}+\frac {t y^{\prime }}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}\frac {\sin \left (2 t \right )}{\cos \left (2 y\right )}+\frac {\ln \left (y\right ) y^{\prime }}{\ln \left (t \right )} = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {t^{2}+1}+y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t +\left (y-3 t \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y-3 t +t y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t y-y^{2}+t \left (t -3 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{2}+t y+y^{2}-t y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{3}+y^{3}-t y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t +4 y}{4 t +y}
\] |
✓ |
✓ |
|
\[
{}t -y+t y^{\prime } = 0
\] |
✓ |
✓ |
|